Contribution of the hexosamine biosynthetic pathway in the hyperglycemia-dependent and -independent breakdown of the retinal neurovascular unit - Wang, Yixin; Eshwaran, Rachana; Beck, Susanne C.; Hammes, Hans-Peter; Wieland, Thomas; Feng, Yuxi (Molecular metabolism, 2023)
Background - Diabetic retinopathy (DR) remains one of the most common complications of diabetes despite great efforts to uncover its underlying mechanisms. The pathogenesis of DR is characterized by the deterioration of the neurovascular unit (NVU), showing damage of vascular cells, activation of glial cells and dysfunction of neurons. Activation of the hexosamine biosynthesis pathway (HBP) and increased protein O-GlcNAcylation have been evident in the initiation of DR in patients and animal models. - Scope of review - The impairment of the NVU, in particular, damage of vascular pericytes and endothelial cells arises in hyperglycemia-independent conditions as well. Surprisingly, despite the lack of hyperglycemia, the breakdown of the NVU is similar to the pathology in DR, showing activated HBP, altered O-GlcNAc and subsequent cellular and molecular dysregulation. - Major conclusions - This review summarizes recent research evidence highlighting the significance of the HBP in the breakdown of the NVU in hyperglycemia-dependent and -independent manners, and thus identifies joint avenues leading to vascular damage as seen in DR and thus identifying novel potential targets in such retinal diseases.